Analisis dan Perancangan UI/UX Aplikasi Mobile eCard Asuransi Takaful Menggunakan Metode Heuristic Evaluation - Eni Pudjiarti; Siti Faizah (Elkom: Jurnal Elektronika dan Komputer, 2025)
Information systems can be technically defined as a set of interconnected components designed to support decision-making and drive organizational operations. PT Asuransi Takaful Keluarga utilizes an information system in the form of the Takaful eCard mobile application, which facilitates registration and access to outpatient and inpatient insurance services at partner hospitals. Over time, several usability issues have emerged related to the application's user interface (UI) and user experience (UX). To evaluate user satisfaction and comfort levels, usability testing was conducted using the Heuristic Evaluation method. This method assesses UI design flaws based on 10 established usability principles. The evaluation revealed design issues in (H2) question Q6, (H3) question Q7, and (H10) questions Q27 and Q28. These issues are primarily related to the absence of new feature additions, ineffective message dialog boxes, and the lack of a user guidance module. The findings highlight the need for UI/UX improvements to enhance user interaction with the Takaful eCard application.